Sonic QP/QS ratio as diagnostic tool for shale gas saturation - Qi, Q.; Müller, T.; Pervukhina, Marina (Society of Exploration Geophysics, 2017)
Sonic QP/QS ratio obtained from full-waveform acoustic logs in conventional sandstone reservoirs is known to be sensitive to the presence of gas, and it is regarded as a potential diagnostic tool for saturation discrimination. However, it is not known if such a saturation diagnostic tool will be applicable in unconventional reservoirs, such as in gas-saturated shales. We have analyzed the monopole and dipole waveform logs acquired from a shale gas exploration well in the Cooper Basin, South Australia. The depth interval of interest is 300 m thick, and it intersects three shale units in which the two underlying formations contain gas saturation of more than 30% and are identified as the primary exploration targets. We use the statistical average method to extract the P- and the S-wave attenuation profiles and obtain an average P-wave quality factor of QP = 33 and S-wave quality factor of QS = 46. The gas saturation of the lithological layers having QP/QS < 1 is appreciably larger than the gas saturation of the others having QP/QS > 1. The net difference indicates that the saturation is a dominant factor in controlling the QP/QS ratio in these shale formations. Based on the criterion QP/QS < 1, we identify the intervals with high gas potential. This result is in good agreement with the prediction from an independently obtained saturation log based on petrophysical analysis. Furthermore, we found that the QP/QS ratio can be jointly interpreted with the VP/VS ratio to differentiate between the saturation and the lithology effects for a shale reservoir interbedded with sandstone layers. Our results underpin the concept of using the QP/QS ratio as a hydrocarbon saturation indicator and provide insights into application of this technique for shale gas detection.